POSTMODERN STUDY WITH REFERENCE TO SELECT WORKS OF SALMAN RUSHDIE - Das, Ravi Bhushan Kumar; Mishra, Sachidanand (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Salman Rushdie’s writings have their own stand in the field of postmodern studies.The basic claim is that because Rushdie's "Midnight's Children" employs a variety of postmodern literary devices, including magical realism, intertextuality, and ambiguity, it is a fine example of a postmodern novel. In addition, the author uses such techniques to discuss a few themes that relate to modern Indian culture and history. The culture has been examined through a line of postmodern criticism that began with the critic use of Irving Howe (1959), Leslie Fiedler and Susan Sontag in the mid-sixties, Ihab Hassan (1969), David Antin (1971), William Spanos (1972) and continued with the criticism of Jean Francois Lyotard, and many others has analyzed the culture. Ironically, the common denominator among these detractors is their failure to agree on a sound, coherent definition of the term "postmodernism."This controversy over a definition of the term has to do with the multiple proliferations of the social, economic, artistic, and cultural trends in the contemporary world.It is difficult to define postmodernism because, as Linda Hutcheon points out, it is a twentieth-century phenomenon that is no longer relevant.It now has its canonical works, anthologies, primers, readers, dictionaries andhistories are fully institutionalized.